Design of CMOS potentiostat for low-concentration heavy metal detection - Raeisinafchi, Mehran (2015)
Metal toxicity is a critical concern in both human and ecosystem health. Many heavy metals are lethal at high concentration. They can also be harmful at trace concentration since accumulating such materials in human organs lead to long-term negative health effects such as heart disease and high blood pressure. Therefore, heavy metal detection of trace concentration is very important. Electrochemical detection system consists of electrodes as transducer, potentiostat as electrical signal detector and data converter for signal processing blocks. The potentiostat detects and amplifies the current generated by the transducer, and it controls the potential of the electrodes. With the advancement of micro- and nano-technology, microelectrochemical system provides feasible solution for sensitive detection and miniaturized platform. Studies have shown that to detect trace concentration of heavy metals, the potentiostat should be able to detect low current typically in the range of nA to μA and a different types of heavy metals can be detected at the potential between -1V and +1V. Researchers have developed CMOS- based potentiostat for detection of limited type of heavy metals and current detection level in μA range using CMOS technology nodes of 0.18μm and above. The research is aimed to design a potentiostat that can detect nA to μA range current and -1V to +1V range of the voltage using 0.13μm CMOS technology with ±1.2 V supply voltage. By using dTo ensure the linearity of output signal, the potentiostat is designed using fully differential operational amplifier and rail-to-rail common-mode range buffer. A new circuit configuration is also proposed to read nA range of current. By using downscaled 0.13μm CMOS technology, the physical layout is reduced to 0.041 ,about 10 times smaller than design area reported particularly using 0.18μm CMOS technology. The post-layout simulation results shows that the proposed design is able to read the input current in the range of nA to μA. The linearity is = 0.999 and also the maximum voltage swing obtained is 2.4 V from -1.2V to +1.2V. The Signal to Noise Ratio (SNR) of CMOS potentiostat for 1nA and 1uA sensor current is equal to 38.91 dB and 47.96 dB, respectively. The circuit developed in this research is verified by using published experimental data for 3mg Cu(II) and 0.6 mM Cd(II). The results shows that the values of current peaks and potentials at which current peaks occur are close to experimental results for these types of heavy metals.